Molecular Docking of Benzoylurea Derivatives as Potential Anti-Breast Cancer Agent and Its Admet Profiles - Siswandono Siswandono (Journal of Global Pharma Technology, 2020)
Objective: At present therapy for breast cancer leads to target cell therapy. One of the compounds that can be developed as anti-breast cancer agents is benzoylurea. Benzoylurea has the same pharmacophore group with hydroxyurea as urea derivatives which have anticancer activity. This study aims to predict the anticancer activity and ADMET profile of seven benzoylurea-derived compounds as candidates cytotoxic agent for breast cancer. Method: Biological activity of benzoylurea derivatives is predicted through molecular modeling (in silico) using the Autodock program, ADME profiles and toxicity can be predicted using the pkCSM program and the Protox II online tool. In silico test was carried out by docking between benzoylurea derivatives and HER2 receptor targets, PDB ID. 3PP0. Result: All benzoylurea-derived compounds studied were compliant with Lipinski's 5 legal requirements. The 4-tertier butylbenzoylurea compound shows a better ADME profile and its toxicity is predicted to have mutagenic properties but not hepatotoxic properties. The smallest docking score of seven benzoylurea derivatives is 4-tertier butylbenzoylurea, therefore the compound has the best cytotoxic activity. Conclusion: the 4-tertier butylbenzoylurea compound is chosen as the compound to be synthesized and further developed.Keywords : molecular docking; benzoylurea; anti-breast cancer; ADMET profiles